Impact of Maternal Aspirin Therapy on Neonatal Epigenetic Patterns - Varotsis, Dante; Betal, Suhita Gayen nee; Addya, Sankar; Aghai, Zubair H.; Boelig, Rupsa C. (American Journal of Perinatology, 2025)
Low-dose aspirin (LDA) is an intervention recommended to prevent the development of hypertensive disorders of pregnancy (HDP) in high-risk pregnancies. Maternal conditions such as HDP have been associated with cord blood epigenetic changes including those related to cardiovascular processes; however, it is unclear whether maternal aspirin therapy may impact neonatal epigenetics in otherwise healthy high-risk pregnancy.This study aimed to determine if maternal LDA exposure in utero leads to altered DNA methylation in umbilical cord blood cells in term neonates compared with controls not exposed to aspirin, and to identify if these methylation changes alter key pathways in the development of chronic disease.Umbilical cord blood was collected from 10 neonates without LDA exposure and 13 neonates with LDA exposure in utero. Patients with hypertensive disorders of pregnancy, COVID-19, and chorioamnionitis were excluded. Genomic DNA was isolated from umbilical cord blood cells and genome-wide DNA methylation was performed using Illumina Methylation EPIC assay.A total of 155 differentially methylated loci (81 genes were hypermethylated and 74 were hypomethylated) were identified in LDA-exposed neonatal umbilical cord blood compared with the control group. Important canonical pathways identified by Ingenuity Pathway Analysis (IPA) were related to Th1 and Th2 signaling and classical (M1) macrophage activation. The genes affected by LDA exposure were associated with cardiac and renal systems.LDA exposure led to differential DNA methylation in umbilical cord blood. The differentially methylated genes were related to inflammatory pathways as well as cardiac and renal toxicity pathways. LDA exposure in utero may promote altered health programming in the neonate in areas impacting cardiovascular health.
Keywords: epigenetic; aspirin; preeclampsia; DNA methylation